Walk the line [videorecording (DVD)] - Mangold, James; Phoenix, Joaquin; Witherspoon, Reese, 1976-; Goodwin, Ginnifer; Patrick, Robert, 1958- (20th Century Fox Home Entertainment, 2006)
Traces Johnny Cash's childhood, including his distant father to his early attempts at a music career. At this point in his life he marries his girlfriend Vivian. During a tour with singer/musicians Elvis and Jerry Lee Lewis, he encounters singer June Carter, and his love for her, and her rejection of him through the years, spurs him into drugs, drinking, and depression. June is both a sassy spitfire singer whose charm breaks hearts and eventually becomes a sympathetic friend who tries to help Johnny get over her. A true love story of two country music stars.